Violence Experiences in Childhood and Adolescence Among Gay Men and Transgender Women Living in Perú: A Qualitative Exploration. Issue 9 (May 2021) - Juárez-Chávez, Elisa; Cooney, Erin E.; Hidalgo, Alberto; Sánchez, Jorge; Poteat, Tonia
The overall goal of this study was to qualitatively explore the different types of violence experienced by gay men (GM) and transgender women (TW) living in Peru during childhood and adolescence, as well as their potential consequences and sources of protection. Participants were selected using purposive sampling. Recruitment took place in a community-based organization in Lima, Peru. In all, 32 GM and 23 TW participated in a total of four Focus Group Discussions (FGD) and 25 in-depth interviews (IDI). Qualitative data collection was conducted between July and October 2016. Four FGD took place with GM ( n = 21) and one with TW ( n = 9). In addition, 11 IDI with GM and 14 with TW were conducted. Data were analyzed using descriptive inductive analysis. Three main types of violence were experienced in childhood and adolescence: (a) violence occurring in the home or otherwise perpetrated by family members, (b) school-based violence, and (c) sexual violence. Both GM and TW experience violence within and outside school and home. School systems should make teachers and parents aware of the impact of homophobic and transphobic bullying and violence. Certain modifications in schools, such as having all-gender bathrooms and promoting activities that are not grounded in gender roles, could be very effective at reducing homophobic and transphobic violence. Schools should also address sexual violence more actively, among both male and female students. Parents' attitudes toward homosexuality and gender diversity need to be addressed by future interventions.